Timeframe Factors of Door-to-Device Time During Pandemic Situation in a Tertiary Cardiovascular Centre in Indonesia - Firdaus, Isman; Juzar, Dafsah Arifa; Dewanggi, Bunga; Nurfitri, Syafira; Utarini, Adi; Djasri, Hanevi (The Indonesian Heart Association, 2023)
Background: The coronavirus disease 2019 (COVID-19) pandemic has greatly affected every aspect of life, especially in the field of cardiovascular services. This creates many challenges in the treatment of highly time-sensitive and potentially lethal conditions such as ST-elevation acute myocardial infarction (STEMI). STEMI patients at high risk for COVID-19 are recommended to be evaluated with additional testing for COVID-19 and possibly require respiratory support, all of which can delay Door-to-device time (DTDT). Objective: In this study, we sought to determine the DTDT for primary percutaneous coronary intervention (PCI) in acute STEMI, the various timeframes influencing the DTDT, and which time factor has the most significant correlation to DTDT in the COVID-19 pandemic era. Methods: A longitudinal retrospective study was conducted at the largest tertiary referral hospital in Indonesia from March 2020 to February 2021. The following timeframes were measured during the study: Door-to-Diagnosis Time [Δt1], Diagnosis-to-Activation Time [Δt2], Informed Consent Time [Δt3], Preparation at Emergency Room (ER) Time [Δt4], Preparation at Catheterization Laboratory Time [Δt6], and PCI Initiation-to-Balloon Time [Δt7]. Spearman’s correlation (ρ) was used to ascertain the correlation among time factors. Results: 238 patients met the inclusion criteria of this study. The observed DTDT was 110 [47 – 437] minutes. Of the variables, DTDT had a strong positive correlation with preparation at the ER time (median 28,0 (1 – 344) minutes; r = 0.702; p-value < 0.0001). Conclusion: This study sheds light on preparation at the ER time as a significant influencing factor for Door-to-device time in the COVID-19 pandemic era.